Efforts to Develop Generation Z Character Education in the Digital Age - Wahab, Wahab; Irpan, Muhammad (AMK : Abdi Masyarakat UIKA, 2024)
This study aims to examine efforts to develop character education for Generation Z in the digital era, marked by rapid technological advancement. Generation Z, born and raised in a digital environment, exhibits characteristics and behavior patterns different from previous generations and is vulnerable to various challenges, such as negative content, cyberbullying, and individualism. Character education is essential in building strong ethics, morality, and personality amidst the dynamics of the digital era. This research employs a literature review method, analyzing various literature on character education in the digital age, particularly focusing on the needs of Generation Z. The study's findings indicate that effective character education for Generation Z must be adapted to technological developments and their unique characteristics. The implementation of digital-based character education strategies involving families, schools, and communities synergistically is a preventive measure to prepare Generation Z to face the challenges of the digital era with a strong and principled character.